Observation of Doppler shift modulated by the internal kink mode using conventional reflectometry in the EAST tokamak - LI, Gongshun; ZHANG, Tao; GENG, Kangning; WEN, Fei; YE, Kaixuan; XU, Liqing; ZHU, Xiang; ZHANG, Xuexi; ZHONG, Fubin; ZHOU, Zhen; YANG, Shuqi; ZHOU, Ziqiang; et al. (Plasma science & technology, 2024)
In this paper we present a new experimental observation using a conventional reflectometry technique, poloidal correlation reflectometry (PCR), in the Experimental Advanced Superconducting Tokamak (EAST). The turbulence spectrum detected by the PCR system exhibits an asymmetry and induced Doppler shift during the internal kink mode (IKM) rotation phase. This Doppler shift is the target measurement of Doppler reflectometry, but captured by conventional reflectometry. Results show that the Doppler shift is modulated by the periodic changes in the effective angle between the probing wave and cutoff layer normal, but not by plasma turbulence. The fishbone mode and saturated long-lived mode are typical IKMs, and this modulation phenomenon is observed in both cases. Moreover, the value of the Doppler shift is positively correlated with the amplitude of the IKM, even when the latter is small. However, the positive and negative frequency components of the Doppler shift can be asymmetric, which is related to the plasma configuration. A simulated analysis is performed by ray tracing to verify these observations. These results establish a clear link between and IKM rotation, and are helpful for studying the characteristics of IKM and related physical phenomena.